Thrombocytopenia in post Covid era: puzzle in the diagnosis. (Bangladesh Journal of Medicine, 2024)
World Health Organization declared the outbreak of coronavirus disease 2019 (COVID-19) a pandemic on March 11, 2020, researchers and clinicians have worked diligently to learn everything about the disease that has resulted in over 240 million cases and nearl y five million deaths worldwide. While most patients who become infected with COVID-19 recover without complications, some patients develop sequelae. One such complication of COVID-19 is immune thrombocytopenia. Immune thrombocytopenia is caused by autoantibodies against platelet antigens, resulting in thrombocytopenia.In the acute setting, ITP appears abruptly, often one to two weeks after a self-limiting Immune thrombocytopenia has been reported in COVID-19 patients. The mechanism of ITP is unclear but can be attributed to the underlying immune dysregulation in COVID-19, leading to the production of antiplatelet antibodies that destroy circulating platelets and megakaryocytes in the bone marrow. The onset of ITP in COVID-19 patients occurs anytime during the disease. However, 20% of ITP cases in a systematic review occurred three weeks after the onset of COVID-19 symptoms, with many occurring after clinic recovery. In some patient, ITP was an incidental finding five weeks after COVID-19 infection and after complete clinical recovery. Different studies revealed about 30% to 40% of COVID-19 ITP patients were asymptomatic. When symptomatic, the commonest symptoms have been cutaneous bleeding, followed by epistaxis. However, severe bleeding, including intracranial hemorrhage and death resulting from hemorrhage, has been reported.Thrombocytopenia in post Covid era so common, difficult to diagnosis and even very much challenging to treat some cases. Though ITP is a diagnosis of exclusion and is diagnosed in patients presenting with thrombocytopenia in which other possible causes of thrombocytopenia have been excluded and assessment of response to treatment. The American Society of Hematology (ASH) recommends testing adults newly diagnosed with ITP for HIV, and hepatitis C. Further investigations are required if there are other abnormalities in the blood count or smear other than thrombocytopenia. Bone marrow biopsies are usually not required in patients presenting with typical ITP. However, in COVID-19 patients who received heparin prophylaxis, heparin-induced thrombocytopenia (HIT) should be excluded. Patients with HIT usually have moderate thrombocytopenia with a platelet count above 50x103/ml and rarely develop severe thrombocytopenia (